THE EFFECT OF CALCIUM CHLORIDE (CaCl₂) CONCENTRATION AND SOAKING DURATION ON THE CHARACTERISTICS OF CANDIED CRYSTAL GUAVA (Psidium guajava) - Devi Paramita; Murhadi; Samsul Rizal; Sri Hidayati (Jurusan Teknologi Hasil Pertanian, 2026)
Crystal guava is a fruit that can be processed into candied fruit. Calcium chloride (CaCl₂) is a food additive that functions as a firming agent and may affect the final quality of the candied guava. This study aimed to determine the effect of CaCl₂ concentration, soaking duration, and their interaction on the characteristics of candied crystal guava. A Completely Randomized Block Design (CRBD) was used with two factors and three replications. The first factor was CaCl₂ concentration: K1 (1%), K2 (3%), K3 (5%). The second factor was soaking duration: L1 (1 hours), L2 (2 hours), L3 (3 hours). The parameters observed included texture, moisture content, pH, sensory properties (texture, taste, and overall acceptance), and calcium content. Data were analyzed using Bartlett‟s and Tukey‟s tests, followed by ANOVA and HSD (Honestly Significant Difference) at a 5% significance level. The results showed that CaCl₂ concentration significantly affected pH and had a highly significant effect on moisture, texture, and sensory characteristics. Soaking duration had a highly significant effect on moisture, texture, and sensory properties, but not on pH. The interaction between both factors had a highly significant effect on sensory properties, but no significant effect on pH, moisture, or texture. The best treatment was 5% CaCl₂ with 3 hours of soaking (K3L3), resulting in a texture of 783.917 gf, moisture content of 79.83%, pH 4.21, texture score of 4.4 (crunchy), taste score of 4.12 (liked), overall acceptance of 4.46 (liked), and calcium content of 339.2 mg/kg.